First-Strike Stability in a Multipolar World - Best, Melvin; Bracken, Jerome (Management Science, 1995)
First-strike stability in a multipolar world measures the incentives of all major nuclear weapon countries, in all possible coalitions, to refrain from preemptive attack. The analysis integrates the interactions of offensive weapon arsenals, vulnerable offensive weapons within these arsenals, defensive weapons, and value targets reflecting the national assets at stake. In the previously-dominant bipolar paradigm, when the United States and the Soviet Union possessed almost all of the strategic nuclear weapons in the world, first-strike stability was an important criterion for assessing defensive deployments of the two sides, without consideration of any other countries. In the emerging multipolar world, however, the United States and Russia are dramatically reducing their offensive forces, and the offensive arsenals of Britain, France, and China are becoming relatively more important. Also, proliferation of medium-range ballistic missiles to other countries capable of attacking Russia, Britain, France, and China; but not necessarily the United States (due to range limitations), greatly complicates the overall situation. The main thrust of this paper is to investigate the first-strike stability implications of the deployment of strategic defenses by the United States and Russia. The principal finding is that in a multipolar world first-strike stability increases with the deployment of small to medium sized strategic defenses whereas in a bipolar world it usually decreases. Although the incentives for the United States and Russia to preempt increase, the incentives of the other countries decrease, with the combined effect over all coalitions of decreasing the incentive to preempt.